Risk of Narrow Upper Airway in Class II Children with Large Horizontal Maxillary Overjet Assessed By Acoustic Reflection: a Case-Control Study - Camilla Hansen; Merete Bakke; Liselotte Sonnesen (eJournal of Oral Maxillofacial Research, 2024)
Objectives: The aim of this case-control study was to examine upper airway by acoustic reflection in class II children with large horizontal maxillary overjet compared to children with neutral occlusion.